Audiovisual-Based Learning for the Shoulder Stand Movement in Floor Gymnastics: An Implementation Study - Rio Wardhani; Zainal Arifin; Ade Rahmat (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: The creativity of teachers in delivering Physical Education learning materials plays a crucial role in ensuring that students receive engaging and varied instruction, which in turn fosters their learning motivation. The primary objective of this study is to examine the effectiveness of using audiovisual media in teaching the shoulder stand movement within floor gymnastics. Furthermore, this study aims to assist students in mastering proper techniques, improving movement accuracy, and enhancing their learning motivation through the implementation of audiovisual-based learning media. Materials and methods: This study employed a quasi-experimental method using a pretest-posttest one-group design. Data analysis was conducted through descriptive statistical techniques, providing an overview of the results based on the mean, standard deviation, as well as the highest and lowest scores. These statistical measures were used to describe the students’ initial and final abilities in performing the shoulder stand movement. Results: During the pretest process, the students’ mean score was 67.19, categorized as fair, while the posttest mean score was 82.67, categorized as good. The population standard deviation in the pretest was 9.71, which is considered relatively high, whereas in the posttest it was 6.33, categorized as relatively low. These results indicate that the use of audiovisual media proved to be effective in helping students achieve a more consistent and comprehensive understanding of the shoulder stand movement. Conclusions: The use of audiovisual media in learning the shoulder stand movement within floor gymnastics has been proven to have a positive effect on students’ learning outcomes. The increase in the mean score reflects an overall improvement in students’ abilities, while the decrease in standard deviation indicates that the students’ learning results became more uniform and consistent. Therefore, audiovisual media is effective as a learning aid to enhance students’ understanding of movement techniques and their skills in performing the shoulder stand in floor gymnastics.